2019
DOI: 10.3390/en12183523
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Measurement Error on England and Wales EPC Ratings

Abstract: Domestic Energy Performance Certificates (EPCs) are used in the UK to provide energy efficiency ratings for use in policy and investment decisions on individual dwellings and at a stock level. There is evidence that the process of creating an EPC introduces measurement error such that repeat assessments of the same property give different ratings, compromising their reliability. This study presents a novel error analysis to estimate the size of this effect, using repeated EPC assessments of 1.6 million existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…While the data-driven EQMs produce similar results throughout all building age classes, the engineering EQM increases in prediction accuracy towards newer buildings until 1990. This is in line with findings in literature of higher measurement errors for buildings with lower energetic efficiency in England and Wales (Crawley et al 2019), thus older buildings with less strict regulations, which can be explained by the underlying data quality. As mentioned, engineering EQMs require exact inputs and expert knowledge to produce viable outcomes.…”
Section: Benchmarking Against the Engineering Energy Quantification Msupporting
confidence: 92%
“…While the data-driven EQMs produce similar results throughout all building age classes, the engineering EQM increases in prediction accuracy towards newer buildings until 1990. This is in line with findings in literature of higher measurement errors for buildings with lower energetic efficiency in England and Wales (Crawley et al 2019), thus older buildings with less strict regulations, which can be explained by the underlying data quality. As mentioned, engineering EQMs require exact inputs and expert knowledge to produce viable outcomes.…”
Section: Benchmarking Against the Engineering Energy Quantification Msupporting
confidence: 92%
“…The climate variables are derived data from re-analysis of multiple original datasets and therefore do not suffer from missing data, although other issues may exist that we have not investigated. EPC data quality has been investigated previously and found to suffer from inaccuracies [24,25]. Researchers are encouraged to treat EPC data with caution and consider potential data quality issues, in addition to the potential bias that requiring an analytic sample to have 100% EPC data will entail (Section 5.4).…”
Section: Data Quality Analysismentioning
confidence: 99%
“…; hence, the need to link the data to a model of buildings and their characteristics. of EPCs and some of their underlying data by the Ministry for Housing, Communities & Local Government (MHCLG) (2017a, 2017b), research has identified considerable uncertainty around the accuracy of ratings and how representative they are of actual energy use (Crawley et al 2019;Jenkins et al 2017;Summerfield et al 2019). These works are important because EPCs are seen by government as a key descriptor of the whole building stock and are used as a means of predicting changes in energy use resulting from the upgrading of building energy performance.…”
Section: Energy Data and Energy Performance Certificates (Epcs)mentioning
confidence: 99%